ปัจจัยที่เกี่ยวข้องกับการใช้ชีวิตโดยอาศัยหลักปรัชญาเศรษฐกิจพอเพียง ด้านการมีภูมิคุ้มกัน ของนักศึกษาระดับอุดมศึกษาในเขตกรุงเทพมหานคร - ลี้ศัตรูพ่าย (Chanya Leesattrupai) ชัญญา (Journal of Behavioral Science for Development, 2016)
(Factors related to lifestyle based on sufficiency economy philosophy, particularly on self-immunity, of undergraduate students in Bangkok metropolitan) Abstract The purpose of this study was to identify factors that predict lifestyle based on sufficiency economy philosophy, particularly on self-immunity, of undergraduate students in Bangkok metropolitan. The study group in this study is 481 second year students of public and a private universities in Bangkok metropolitan, using multi-stage sampling method in various levels: at university, faculty, and majors level. The findings show that there is .01 statistically significance on personal and social factors indicating lifestyle based on sufficiency economy philosophy, with role model of life style based on sufficiency economy philosophy of self – immunity at the highest (b=.272). The next highest predictor is the attitude towards lifestyle based on sufficiency economy philosophy, focusing on self-immunity at (b=.210). The next indicator is the peer group influence at (b = .188). And the last predictor is future orientation and self – control characteristics at (b = .152). These four predictors are able to predict at 40% total, with .01 statistical significance. Keywords: sufficiency economy philosophy, self - immunity, future orientation and self – control characteristics, attitude, peer group influence